The results of sphincterometry in patients after sorgion treatment of extrasphintery anal fistula - Paliyenko, R.; Mishura, Z. (Journal of Education, Health and Sport, 2021)
More than 30% of patients with chronic paraproctitis have complex forms. They are most often complicated by external sphincter insufficiency due to deformation of the anal canal and scarring of the sphincters. The main principle of substantiation of surgical treatment of extrasphincteric pararectal fistulas is the individual choice of method in each particular patient. It is based on a comprehensive assessment of such factors as the etiology of the fistula, its distance from the edge of the anus, the relationship of the defect or fistula with the sphincter muscles apparatus, the severity of the scarring process, the functional state of the rectum. Aim. Evaluation of the functional state of the sphincter apparatus of the rectum in patients with extrasphincteric pararectal fistulas in the preoperative, early and late postoperative periods. Materials and methods. To determine the average indicators of anal sphincter function, basal tone and maximal compression force were measured using a sphincterometer "Sphinctometer STM-0164-SM" in 114 healthy individuals (68 men and 46 women) of different ages (16 to 80 years) who objectively had no signs of anal incontinence. In all patients, sphincterometry was preceded by a thorough proctological examination, and proctological pathology was excluded. Therefore, hemorrhoids or anal fissures, which lead to increased basal tone at rest, were excluded so as not to lead to falsified values. Results. Indicators of the maximum compression force in the early postoperative period, ie the compression force of the external anal sphincter, in both groups were significantly lower than preoperative and ranged from 55 to 154 mm Hg, respectively. and from 63 to 137 mm Hg. This can be explained by the presence of a granulating wound in the pararectal tissue, edema and partial injury of the external anal sphincter during surgery. In the late postoperative period, 6-12 months after surgery, the indicators of basal tone in both groups approached the preoperative indicators. In the main group, the study was performed in 22 patients. In these 22 patients, the tone of the internal anal sphincter did not differ significantly from the preoperative and ranged from 20 to 37 mm Hg. In the control group, in all 32 patients, the basal tone of the anal sphincter was significantly lower than before surgery - from 17 to 28 mm Hg. There were no clinical manifestations of incontinence at rest in either main or control groups. In the late postoperative period in both groups a decrease in the maximum compression force of the external anal sphincter was revealed. In the main group the maximum compression force of the external anal sphincter varied from 71 to 186 mm Hg, and in the control group from 77 to 135 mm Hg, respectively. Conclusion. Surgical treatment of patients with extrasphincteric pararectal fistulas significantly reduces the contractile function of the external anal sphincter in the postoperative period, regardless of the choice of surgery.